2014
DOI: 10.3390/cancers6020756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Premalignant and Tumor Microenvironment on Immune Cell Cytokine Production in Head and Neck Cancer

Abstract: Head and neck squamous cell carcinoma (HNSCC) is marked by immunosuppression, a state in which the established tumor escapes immune attack. However, the impact of the premalignant and tumor microenvironments on immune reactivity has yet to be elucidated. The purpose of this study was to determine how soluble mediators from cells established from carcinogen-induced oral premalignant lesions and HNSCC modulate immune cell cytokine production. It was found that premalignant cells secrete significantly increased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…Previously, our lab had shown that premalignant lesion cells established from the 4-NQO murine model of oral carcinogenesis secrete increased levels of several immune modulating factors, including PGE 2 , compared to HNSCC cells (27). The current study shows that treatment of premalignant lesion cells with indomethacin, a pan-COX inhibitor, increased their induction of spleen cell production of Th1-associated cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, our lab had shown that premalignant lesion cells established from the 4-NQO murine model of oral carcinogenesis secrete increased levels of several immune modulating factors, including PGE 2 , compared to HNSCC cells (27). The current study shows that treatment of premalignant lesion cells with indomethacin, a pan-COX inhibitor, increased their induction of spleen cell production of Th1-associated cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cell lines were established, as previously described (27) by excising 4-NQO-induced premalignant lesions or HNSCC from the tongues of premalignant lesion- or HNSCC-bearing mice at the appropriate stage, as defined through histopathological analysis by the oral pathology section in the Center for Oral Health Research at the Medical University of South Carolina. Briefly, excised premalignant lesions or HNSCC tumors were placed into culture and, once adherent cells became established, non-adherent cells were removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stromal microenvironment within the colon is comprised of extracellular matrix components, secreted factors, and stromal cells, which include fibroblasts as well as resident and infiltrating immune cells. Previous studies of premalignant changes associated with cancer, including head and neck (21), breast (22) and ovarian (23) cancers, have found evidence for a pro-inflammatory stromal microenvironment. Characteristic changes include increased cytokine signaling and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck cancer for example, the premalignant microenvironment elicits pro-inflammatory cytokine production, in contrast to the tumor microenvironment, which is less immune stimulatory [15]. Alterations in the microenvironment can be present early before changes in the epithelial cells or these changes may be a reaction to excess proliferation of premalignant or malignant cells [16].…”
Section: The Molecular Basis For Cancer Preventionmentioning
confidence: 99%